Five and four dimensional experiments for robust backbone resonance assignment of large intrinsically disordered proteins: application to Tau3x protein - Żerko, Szymon (J Biomol NMR, 2016)
New experiments dedicated for large IDPs backbone resonance assignment are presented. The most distinctive feature of all described techniques is the employment of MOCCA-XY16 mixing sequences to obtain effective magnetization transfers between carbonyl carbon backbone nuclei. The proposed 4 and 5 dimensional experiments provide a high dispersion of obtained signals making them suitable for use in the case of large IDPs (application to 354 a. a. residues of Tau protein 3x isoform is presented) as well as provide both forward and backward connectivities. What is more, connecting short chains interrupted with proline residues is also possible. All the experiments employ non-uniform sampling. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10858-016-0048-7) contains supplementary material, which is available to authorized users.